Holoportation: Virtual 3D Teleportation in Real-Time - Orts-Escolano, Sergio; Rhemann, Christoph; Fanello, Sean; Chang, Wayne; Kowdle, Adarsh; Degtyarev, Yury; Kim, David; Davidson, Philip L.; Khamis, Sameh; Dou, Mingsong; Tankovich, Vladimir; Loop, Charles; et al. (UIST 2016, 2016)
Holoportation is a new type of 3D capture technology that allows high quality 3D models of people to be reconstructed, compressed, and transmitted anywhere in the world in real-time. When combined with mixed reality displays such as HoloLens, this technology allows users to see and interact with remote participants in 3D as if they are actually present in their physical space. Communicating and interacting with remote users becomes as natural as face to face communication.